The phenotypic spectrum of WWOX-related disorders: 20 additional cases of WOREE syndrome and review of the literature - Piard, J; Hawkes, L; Milh, M; Villard, L; Borgatti, R; Romaniello, R; Fradin, M; Capri, Y; Héron, D; Nougues, M; Nava, C; Arsene, O; et al. (Springer Nature, 2018)
Purpose Germline WWOX pathogenic variants have been associated with disorder of sex differentiation (DSD), spinocerebellar ataxia (SCA), and WWOX-related epileptic encephalopathy (WOREE syndrome). We review clinical and molecular data on WWOX-related disorders, further describing WOREE syndrome and phenotype/genotype correlations. Methods We report clinical and molecular findings in 20 additional patients from 18 unrelated families with WOREE syndrome and biallelic pathogenic variants in the WWOX gene. Different molecular screening approaches were used (quantitative polymerase chain reaction/multiplex ligation-dependent probe amplification [qPCR/MLPA], array comparative genomic hybridization [array-CGH], Sanger sequencing, epilepsy gene panel, exome sequencing), genome sequencing. Results Two copy-number variations (CNVs) or two single-nucleotide variations (SNVs) were found respectively in four and nine families, with compound heterozygosity for one SNV and one CNV in five families. Eight novel missense pathogenic variants have been described. By aggregating our patients with all cases reported in the literature, 37 patients from 27 families with WOREE syndrome are known. This review suggests WOREE syndrome is a very severe epileptic encephalopathy characterized by absence of language development and acquisition of walking, early-onset drug-resistant seizures, ophthalmological involvement, and a high likelihood of premature death. The most severe clinical presentation seems to be associated with null genotypes. Conclusion Germline pathogenic variants in WWOX are clearly associated with a severe early-onset epileptic encephalopathy. We report here the largest cohort of individuals with WOREE syndrome.